It is the Spirit Who Gives Life : New Directions in Pneumatology - Bordeianu, Radu (Book collections on Project MUSE., 2022)
"This volume gathers essays authored by eleven world-renowned theologians. Each contribution originated as a public lecture addressed to theologians and an educated general audience, followed by a private colloquium in which the lecturers conferred with scholars who are experts in the field. Thus, the present volume offers a multifaceted approach to Pneumatology, in an ecumenical spirit"--